Вентиляційні процеси та теплообмін при обтіканні неізотермічних поверхонь пристінним турбулентним струминним потоком - Горобець, В. Г.; Лисиченко, М. Л.; Синявський, О. Ю. (Енергетика і автоматика, 2017)
UDC  536.24VENTILATION PROCESSES AND HEAT EXCHANGE AT FLOWING AROUND OF UNISOTHERMAL SURFACES OF TURBULENT WALL JET STREAM V. Gorobets, N. Lisichenko, A. SinyavsryWall jet streams are widely used for ventilation processes, heating and cooling of various materials in industrial and agriculture sectors. To intensify the transfer processes, reducing time flow heat exchange processes and to improve processes using near-wall jet flows used turbulent heating and cooling surfaces. In this case is used approach unlike the methods of calculation for laminar flow regimes in which case the need to develop special methods. These methods on semiempirical equation of turbulent energy and mass transfer for external coolant are based.The purpose of the work. A method for calculating heat transfer during turbulent flow around the surfaces of the wall jet streams using integrated methods for solving transport equations should be developed.The calculation method for heat transfer conditions at the wall jet flow around of unisothermal bodies in conditions of turbulent flow regime is developed. The technique is based on the use of Prandtl hypothesis for the turbulent boundary layer and selecting the interpolation functions that describe the velocity distribution in this layer.The technique is based on the use of L. Prandtl hypothesis for turbulent flows, approximation of actual speed profiles in the boundary layer byapproximation functions and choice of turbulence constants witch based on the experimental data.An overall functional relations between the density of heat flux and temperature gradient at the unisothermal surface based is found using the integrated methods for solving of the boundary layer equations.Numerical values witch are included in the functional relations between the density of heat flux and non-isothermal temperature gradient at the surface are calculated.The developed calculation methods of heat transfer for case of wall turbulent jet flows can be used to calculate the various heat exchangers, in which there are considered current conditions coolants should be used.